Technological developments in networking, education and automation - Elleithy, Khaled. (Springer Netherlands :, 2010)
Technological Developments in Networking, Education and Automation includes a set of rigorously reviewed world-class manuscripts addressing and detailing state-of-the-art research projects in the following areas: Computer Networks: Access Technologies, Medium Access Control, Network architectures and Equipment, Optical Networks and Switching, Telecommunication Technology, and Ultra Wideband Communications. Engineering Education and Online Learning: including development of courses and systems for engineering, technical and liberal studies programs; online laboratories; intelligent testing using fuzzy logic; taxonomy of e-courses; and evaluation of online courses. Pedagogy: including benchmarking; group-learning; active learning; teaching of multiple subjects together; ontology; and knowledge management. Instruction Technology: including internet textbooks; virtual reality labs, instructional design, virtual models, pedagogy-oriented markup languages; graphic design possibilities; open source classroom management software; automatic email response systems; tablet-pcs; personalization using web mining technology; intelligent digital chalkboards; virtual room concepts for cooperative scientific work; and network technologies, management, and architecture. Coding and Modulation: Modeling and Simulation, OFDM technology , Space-time Coding, Spread Spectrum and CDMA Systems. Wireless technologies: Bluetooth , Cellular Wireless Networks, Cordless Systems and Wireless Local Loop, HIPERLAN, IEEE 802.11, Mobile Network Layer, Mobile Transport Layer, and Spread Spectrum. Network Security and applications: Authentication Applications, Block Ciphers Design Principles, Block Ciphers Modes of Operation, Electronic Mail Security, Encryption & Message Confidentiality, Firewalls, IP Security, Key Cryptography & Message Authentication, and Web Security. Robotics, Control Systems and Automation: Distributed Control Systems, Automation, Expert Systems, Robotics, Factory Auto Education in the Clouds: How Colleges and Universities are Leveraging Cloud Computing -- Weak Orderings of Knowledge States -- Problem Based Learning: Obtaining Enzyme Kinetics Parameters Integrating Linear Algebra, Computer Programming and Biochemistry Curriculum -- Adaptive Assessments using Open Standards -- Online Academic Advising Support -- Using Computer Game to Share knowledge -- Following the Paper Trail: Measuring the Economic and Environmental Impact of Digital Content Delivery -- Context Driven Personalized e-Learning Environment Provided as a State Service -- Exploring Teachers’ Beliefs about Digital Citizenship and Responsibility -- Faculty Driven Assessment of Critical Thinking: National Dissemination of the CAT Instrument -- Enhancing the Instruction of Introductory Electric Circuit Courses using MATLAB -- Istopolis: Design Issues and Evaluation’ Results of an Integrated Web-Based Educational Application -- TEAC2H-RI: Educational Robotic Platform for Improving Teaching-Learning Processes of Technology in Developing Countries -- Selecting Patterns for the Evaluation of Systems -- Effectiveness of Collaborative Learning in Teaching Information Systems -- Implementation of a Curriculum Management System at a Faculty of Medicine – Lessons Learned from a Pilot Project -- Use of Ontology for Reusing Web Repositories for eLearning -- Actual and Future Trends of the E-education and Its Costs Specification in the Czech Republic -- Modern Improvements in the Digital Logic Laboratory -- e-Cheating and Calculator-Technology -- Perspectives on Critical Thinking through Online Discussion Forums in Engineering Mathematics -- Digital System Description Knowledge Assessment -- Wikibooks as Tools for Promoting Constructivist Learning in Higher Education: Findings from a Case Study -- The Impact of the Context of an Information System on Strategic Information Quality - The Institute of Technology Sector in Ireland -- Can Mobile Computin